Studying a relationship between Health Services Indictors and Human Development Indictors by using Canonical Analyzes - Al-Ali, Ibrahim; Dribati, Yasserh; Ahmed, Wasem (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims to examine the relationship between the health service indicators and indicators of human development in the province of Latakia using Canonical analysis, and the importance of the research being brings us to the Canonical analysis of the model shows the impact of health services variables in human development variables, and it was the most important results that have been reached: -The Statistically significant relationship between the health service indicators and indicators of human development in Latakia, where it was found that the intensity of the relationship 0.998 which shows a very solid relationship. - Turned out to be the most influential health variables in the canonical compound U1 is the variable X1 which stands for the average number of doctors When X1 increases by one the variable U1 would be increased by (48.590). - Turned out to be more developmental variables influence the canonical compound V1 is the variable Y3, which symbolizes the crude death rate When Y3 is increased by one, the V1 would be increased by (1.723). دراسة العلاقة بين مؤشرات الخدمات الصحيّة ومؤشرات التنمية البشريّة في محافظة اللاذقيّة باستخدام التحليل القانوني يهدف هذا البحث إلى دراسة العلاقة بين مؤشرات الخدمات الصحيّة ومؤشرات التنمية البشريّة في محافظة اللاذقيّة باستخدام التحليل القانوني, وتأتي أهميّة البحث من كونه يوصلنا إلى نموذج ارتباط قانوني يوضّح أثر متغيرات الخدمات الصحيّة في متغيرات التنمية البشريّة, وكان من أهمّ النتائج التي تمّ التوصّل إليها: -هنالك علاقة ذات دلالة إحصائيّة بين مؤشرات الخدمات الصحيّة ومؤشرات التنمية البشريّة في محافظة اللاذقيّة, وأنّ شدة هذه العلاقة هي 0.998 وهي تدل على علاقة متينة جدّاً. -تبيّن أنّ أشدّ المتغيرات الصحيّة تأثيراً في المركّب القانوني U1 هو المتغيّر X1 الذي يرمز لمعدّل عدد الأطباء فعندما يزداد X1 بمقدار واحد فإن المتغير U1 سيزداد بمقدار (48.590). - تبيّن أنّ أكثر المتغيرات التنمويّة تأثيراً على المركّب القانوني V1 هو المتغير Y3 الذي يرمز لمعدّل الوفيّات الخام فعندما يزداد Y3 بمقدار واحد فإن V1 سيزداد بمقدار (1.723).